Perturbações somatoformes - revisão da epidemiologia nos cuidados primários de saúde. - Cristina Fabião; Maria Carolina Silva; Manuela Fleming; António Barbosa (Acta Médica Portuguesa, 2010)
The prevalence of somatization is dependent on the classification methods and measures used to define it and the context from which the collected data are gathered. The aim of this study was to compare the prevalence of somatization and Somatoform Disorders (SFD) in Primary Health Care.A systematic review of the studies of the prevalence of somatization and SFD in PC (Primary Care) was made, from July 1998 to June 2009. The key words of this investigation, in Pub Med, were; somatoform disorders; somatization; somatisation; medically unexplained symptoms; MUS; functional somatic symptoms, the link with each of these key words having been made to Primary Care. A grid was drawn up for the selection of each article. The criteria for the inclusion of the studies took into account aspects related to the methodology and the instruments used (use of interview) and the clear definition of medically unexplained symptoms, amongst others.Twelve studies with prevalence values in a PC setting and 1 study of metaanalysis were selected. The values found for the total prevalence of SFD were extremely disperse, taking into consideration the various studies, being between 12% and 57.9%. The same results were found in relation to somatization disorder (between 0.5% and 16.1%) with 10.1%, referred to one study, following the very restrictive criteria of ICD-10. Results were more homogeneous for somatization defined by more abridged criteria, the Somatic Symptom Index 4.6 (SSI4,6) presenting values around 20% in almost the majority of selected studies that estimate the prevalence following this criteria. In the great majority of the studies, SFD increased the relative risk of other mental disorders (depressive and anxiety disorders). Some studies concluded that there was a relative independence of somatization in relation to those disorders, certified by the existence of a specific and cumulative effect of somatization (in relation to depressive and anxiety disorders) on the level of disability and of functional limitations as well as the level of use of resources in PC.This last decade has enabled a group of new studies that allow us to understand the extent of somatization in PC, especially in Europe and North America, and to have a more clearly based idea of the needs at service level and investigation level, within the referred area.